Decision Support System for Determination of Village Fund Allocation Using AHP Method - Vasma Vitriani Sianipar; Anjar Wanto; M Safii (The IJICS (International Journal of Informatics and Computer Science), 2020)
This study aims to describe the management of the allocation of village funds in physical development in the village of Siborna, Panei Subdistrict, Simalungun Regency and to identify inhibiting factors and supporting factors in managing village fund allocation. The focus of this research is the management of village fund allocations which include: planning, implementation. The determination of the allocation of village funds will later use the Analytical Hierarchy Process (AHP) method with 4 criteria including: villagers, rural poor, village area and Village Geographical Difficulty Index. Alternative Samples in this study were 4 villages, including the villages of Sosor Hamlet, Simpang Bahbirong Hamlet, Hutabagasan Hamlet and Kebun Sayur Hamlet. The results of this study using the AHP method obtained by the Village of Vegetable Farm Village is an alternative with the highest value that is eligible to get a village fund allocation from the government with a value of 3,0000